Development of a Google Sites–Based Interactive E-Module for the Creative Products Course among Eleventh-Grade Office Management Students at SMK Negeri 12 Jakarta - Anisah Farah Rafidah; Darma Rika Swaramarinda; Ferry Setyadi Atmadja (The Future of Education Journal, 2026)
This study aimed to develop an interactive e-module using the Google Sites platform as a feasible learning medium for classroom instruction. The research employed a Research and Development (R&D) approach utilizing the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The product validation process involved three experts, namely a subject matter expert, a media expert, and an instructional design expert. The validation results indicated that the Google Sites–based interactive e-module was highly feasible for instructional use, achieving validation scores of 98% from the subject matter expert, 88% from the media expert, and 92% from the instructional design expert. Subsequently, product revisions were made based on the suggestions and feedback provided by the validators. Furthermore, the effectiveness test yielded an N-Gain score of 0.90, which falls into the high category, indicating that the interactive e-module significantly improved students’ understanding. This improvement was supported by the systematic organization of learning materials, interactive visual features, and ease of access across various digital devices. The developed media facilitates flexible and independent learning while aligning with the principles of the Merdeka Curriculum implemented in vocational high schools. Therefore, the Google Sites–based interactive e-module can serve as an effective and innovative learning medium to enhance students’ learning outcomes.